Long‐Time Relaxation Induced by Dynamic Forcing in Geomaterials. Issue 5 (30th May 2019) - Ostrovsky, L.; Lebedev, A.; Riviere, J.; Shokouhi, P.; Wu, C.; Stuber Geesey, M. A.; Johnson, P. A.
Abstract: We present a theoretical model and experimental evidence of the long‐time relaxation process (slow dynamics) in rocks and other geomaterials following a dynamic wave excitation, at scales ranging from the laboratory to the Earth. The model is based on the slow recovery of an ensemble of grain contacts and asperities broken by a mechanical impact. It includes an Arrhenius‐type equation for recovery of the metastable, broken contacts. The model provides a characteristic size of the broken contacts (order 10 −9 m) and predicts that their number increases with impact amplitude. Theoretical results are in good agreement with the laboratory and field data in that they predict both the logarithmic law of recovery rate and deviations from this law. Key Points: Many geomaterials are characterized by strong hysteretic nonlinearity and the long‐time relaxation after an impact (slow time) Laboratory experiments and seismic measurements reveal a typical logarithmic law of recovery of elastic moduli of rock in time The suggested theory explains such behavior for a broad range of geomaterials at scales from the laboratory to Earth